Crack Growth Behavior of Welded Stiffened Panel. (2015) - Sepe, Raffaele; Armentani, Enrico; di Lascio, Pasquale; Citarella, Roberto
Abstract: Fatigue crack growth experimental tests and numerical analyses on Friction Stir Welding (FSW) welded flat stiffened panels were performed in order to assess their fracture resistance capability. Panels and stiffeners are made of aluminum alloy 2024-T3. Linear elastic FEM (Finite Element Method) and DBEM (Dual Boundary Element Method) stress analyses were performed to simulatecrack growth, obtaininga satisfactory correlation againstexperimental outcomes.